INFLUENCE OF CREDIT MANAGEMENT ON FINANCIAL INTERMEDIATION EFFICIENCY OF DEPOSIT TAKING SACCOS'S IN KENYA - Muriithi, Perminus Kariuki; Nasieku, Tabitha; Memba, Florence (Journal of Accounting, 2022)
Purpose: The regulation of Deposit Taking Saving and Credit Co-operative societies was expected to enhance transparency and accountability in the management of DT SACCO's and thus protecting the interests of members. This was expected to lead to better service to members through provision of timely loans and advances with minimal risk exposures. SACCO's have been identified as major financial player away from the Commercial Banks thus important in financial intermediation. Thus, the current study on the influence of credit management on financial intermediation efficiency of DT SACCO's in Kenya. Methodology: The study targeted 174 DT SACCO's operating in Kenya as at 31st December 2019. Data analysis was done using both descriptive and inferential statistics. Descriptive statistics used in the study included measures of central tendency; mean; dispersion and standard deviation. Inferential statistics used included correlation and regression analysis. Results: The study findings showed that there was a persistent increase in financial intermediation efficiency within the period under study and thus can be concluded that as DT SACCOs complied with credit managementon their financial intermediation efficiency improved. Unique Contribution to Theory, Practice and Policy: Pure efficiency was lower than scale efficiency throughout the period under study, thus there is need for management to examine their performance inefficiencies so as to minimize wastages and spillage of performance opportunities.